Impact of COVID-19 Pandemic on Homecare Delivery—A Comparative Study - Malik E. (My University, 2025)
Background: The COVID-19 pandemic has generated significant interest among researchers from diverse fields. One such field is homecare, which is also one of the most severely impacted domains in the healthcare ecosystem. Purpose: This paper aims to present a comparative study between the self-managed homecare organizations and the conventional homecare organizations dealing with homecare delivery amidst the constraints and consequences of the COVID-19 pandemic. Their context also includes the COVID-19 accelerated growth and proliferation of the Fourth Industrial Revolution (4IR) technologies. Method: The methodology used in the study is a case study method, a popular qualitative research method. This study includes a comparative analysis of conventional (Portea Medicals) and self-managed homecare using a case of Buurtzorg India across dimensions of associated challenges and advantages. Results and Discussion: The services’ discontinuity of homecare organizations in public health systems during pandemics (especially accompanied by co-morbidity) can increase the mortality rates. Self-managed homecare organizations seemed to be better suited to maintain service continuity due to their greater flexibility to changing environments or VUCA contexts, better decision making in action owing to the decentralization of authority, humanistic, and a holistic approach seeking the welfare of all the concerned entities. Homecare organizations are also at considerable risk of such infections caused by patients to nursing staff or from nursing staff to the patients, i.e., cross-infections. Originality: Given the literature review on the COVID-19-related homecare delivery domain, there is no similar comparative study of traditional and self-managed care in a pandemic context like COVID-19. The present study aims to fill this research gap for potential usefulness in dealing with homecare delivery in pandemic contexts. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd 2023.